Color Linguistics As A Key To Understanding And Translating The Imaginative Structure Of A Literary Text (Diversity Research: Journal of Analysis and Trends, 2025)
The article is devoted to the linguistics of color as an urgent general method of linguistic research into color and as instruments of translation of texts containing terms of color (words with a color component). The problems of such translation are presented in the article against the background of theoretic aspects of linguistics of color as a sphere of contemporary linguistic studies. The linguistics of color is represented as a widely elaborated sphere of linguistic knowledge which has its worked-out notable directions, research institutions and a range of investigating problems. The basic concepts of the linguistics of color are analyzed from the perspective of pragmatics and are embodied into the practice of translation. Linguistics of color's critical apparatus is considered on the basis of linguistic colorimetry as a collection of particular methods contributing to understanding and translation of texts with color terms. The comprehension of color terms and possibilities of their translation depend on determining their role in the lexical systems of both the source and target languages and their place in the linguistic worldviews.